Virtual Tour 360 Museum Matrilineal - Putri Rahmadhani; San Ahdi (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The Matrilineal Museum is a management forum that supports efforts to preserve cultural values ​​related to the matrilineal system in Minangkabau, having its address at Jalan Raya Belimbing, Kuranji Padang. In this problem, museum tourist visits have decreased since 2019. Information about the Matrilineal Museum can be accessed by using posters, the web or simply via the address on Google maps as well as limited print media such as books. The purpose of this design is to increase public interest in visiting the Matrilineal Museum through virtual tour 360 media. At the design stage using the 4D method, Define, Design, Develop, and Disseminate. the analysis used is SWOT analysis. Video Virtual Tour 360 Matrilineal Museum, Center for Preservation of Cultural Values ​​of West Sumatra, will be implemented into supporting media